2018
DOI: 10.1039/c8cc02801j
|View full text |Cite
|
Sign up to set email alerts
|

In situ identification of cation-exchange-induced reversible transformations of 3D and 2D perovskites

Abstract: The optical and structural properties of hybrid perovskites can be tuned by the post-synthetic introduction of new cations. To advance the development of this approach, knowledge of the reaction mechanism is essential, but has not yet been elucidated. Here, the effect of n-octylamine on three-dimensional (3D) methylammonium lead bromide (MAPbBr3) was investigated by in situ X-ray photoelectron spectroscopy. Spectroscopic analysis indicated equimolar substitutions between octylammonium (OcA+) and methylammonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…This mechanism reorganizes the surface to form the 2D perovskite. , The greater complexation of Pb 2+ with Br – than with I – justifies the greater bromine/iodine ratio in the 2D phase than in the 3D perovskite . Due to the highly polar nature of IPA, it significantly dissolves FA and MA ions .…”
Section: Resultsmentioning
confidence: 99%
“…This mechanism reorganizes the surface to form the 2D perovskite. , The greater complexation of Pb 2+ with Br – than with I – justifies the greater bromine/iodine ratio in the 2D phase than in the 3D perovskite . Due to the highly polar nature of IPA, it significantly dissolves FA and MA ions .…”
Section: Resultsmentioning
confidence: 99%
“…, where N is the concentration of atoms, I is the peak area of photoelectrons, and S is the atomic sensitivity factor provided by the instrument manufacturer. All spectra were calibrated to their corresponding C 1s which is 285.3 eV, 28,29 and binding energy values for all fitted and assigned spectral peaks are stated with an accuracy of 0.1−0.2 eV. Detailed femtosecond time-resolved transient absorption spectra were described in literature.…”
Section: Methodsmentioning
confidence: 99%
“…The ratios of I/Sn, Br/Sn, N/Sn, and Pb 0 /Pb total were estimated from the following equation: , where N is the concentration of atoms, I is the peak area of photoelectrons, and S is the atomic sensitivity factor provided by the instrument manufacturer. All spectra were calibrated to their corresponding C 1s which is 285.3 eV, , and binding energy values for all fitted and assigned spectral peaks are stated with an accuracy of 0.1–0.2 eV.…”
Section: Methodsmentioning
confidence: 99%
“…The first two peaks have the same locations as those of the DMEDAI 2 powder, but the last three peaks located at 1021, 857, and 755 cm −1 were not observed in the spectra of DMEDAI 2 or MAPbI 3 , likely corresponding to the newly formed 2D perovskites. These results suggested that DMEDAI 2 did not physically attach to the surfaces of MAPbI 3 but underwent cation exchange with MA in 3D MAPbI 3 or reacted with PbI 2 to form 2D perovskites, 58,59 which changed the structural and optical properties of the pristine MAPbI 3 thin films.…”
Section: Resultsmentioning
confidence: 99%